พฤติกรรมตามแนวคิดการบริโภคที่ยั่งยืนของคนวัยทำงานในอำเภอฝาง จังหวัดเชียงใหม่ต่อการซื้อรถจักยานยนต์ - อ้อย ทิพโรจน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Aim of this independent study is study to behavior regarding to sustainable consumption concept of working-age people in fang district, Chiang Mai province towards purchasing a motorcycles. The questionnaire was used as the tool to collect data 400 using a quota sampling by occupation. Data were analyzed using descriptive statistics. The results presented that most respondents were married female, aged of 49-50 years old, with bachelor’s degree. The majority was the employee of private company and earned the monthly income at the amount of 5,001-10,000 baht. As a result, the respondents purchase motorcycle gear is motorcycle categories, size 101-125 cc, brand Honda and purchase price 40,001-50,000 baht cash payment. Futuremore the purpose is buy more of the same and use it for shopping or errands little. Moreover, the reasons to buy not only fuel economy but also gender respondents their own. Likewise, consumer buying from major distributors. Consumers recognize motorcycles from the media, television and promotions favorite is the giveaway. Cluster Analysis was used to explain the difference of consumer groups of the sample. The results were divided into two groups, consumer groups are a group of motorcycle buyers are consumers who are aware of the concept of sustainable consumption and general consumers. The most people are consumers who are aware of the concept of sustainable consumption 77 percent. According to the correlation analysis on general information of working-age people who bought a motorcycle, as divided into a group of working-aged consumers with sustainable consumption concept and a group of general, the results presented that the difference of personal factors on education background, career, average monthly income and the number of motorcycles in the family affected the correlation of these two groups. Nevertheless, the difference of personal factors on gender, age, marital status and number of family members did not affect the correlation among these two groups. Based upon the study on behavioral classification on the sustainable consumption concept towards purchasing a motorcycles of these two groups of consumers, the results suggested that the consumer behaviors on brand, size of motorcycles, the cost of purchasing, terms of payment, purpose of use the main objective, Influential individuals in deciding, channel, information sources and the promotion is giveaway affected to both groups of consumers. According to the study on statistic test of difference, the findings presented that both groups of consumers to focus on different marketing mix and consumer awareness of sustainable consumption concept is more important than general consumers. Product is differently paid importance to the following sub-factors: the brand, feature, save fuel, the after-sales service and manufactured environmentally friendly. Price: reasonable pricing, spare parts and service reasonable price and the price corresponds with the economic. Place: the reliability of the dealer location, the display of merchandise, time to open - closed and product varieties. However, the promotion consumers were two groups were not significantly different.